Explore what factors can influence the product’s country of origin. Explore how country of origin influences consumer behavior and Porto wine brand. A conceptual model is proposed to clarify the COO and other variables relationships on Porto wine, representative factors: ethnocentrism, cosmopolitanism, affinity, attitude toward brand of wine, brand equity, willingness to buy, memorability, brand identification, brand affect - Zhou, Xiaoli (2020)
Dissertação de Mestrado em Marketing apresentada à Faculdade de Economia